Radzenie sobie ze stresem przez dzieci w warunkach zmian spowodowanych chorobą przewlekłą = Coping with stress by children in conditions of change caused by chronic disease - Pawluk-Skrzypek, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article provides an overview. It presents the concept of health and illness and outlines the problem of changes experienced by a child as a result of his or her illness. It describes the phenomenon of stress, and reviews studies into a child?s strategies for coping with the stress caused by this situation. The article also points to the most important predictors regarding the desired, i.e. active, ways of coping with stress caused by a chronic disease in children.
Keywords: dziecko; stres; choroba przewlekła; radzenie sobie; child; chronic disease; stress; coping